Persepsi Pelayanan dan Minat Nasabah Bank Syariah Indonesia: Peran Religiusitas Islam sebagai Pemoderasi - Arifin, Muhammad; Amri, Khairul (Jurnal EMT KITA, 2024)
This research investigates the functional relationship between customers’ interest in using Islamic banking services and service quality by placing Islamic religiosity as a moderator variable. The research sample consisted of 231 financing customers of Bank Syariah Indonesia in Banda Aceh, selected through purposive sampling. Data collection was conducted through a questionnaire, and the data were analyzed using the Moderated Regression Analysis (MRA) statistical model. The research findings reveal that services have a positive and significant impact on customers’ interest in using financing services. Similarly, Islamic religiosity also has a positive and significant influence. However, Islamic religiosity plays a negative moderating role in the relationship between customer interest and services. The positive impact of services on customer interest decreases with the increasing level of Islamic religiosity.